Applications of group theory to combinatorics : selected papers from the Com²MaC Conference on Applications of Group Theory to Combinatorics, Pohang, Korea, 9-12 July 2007 /: selected papers from the Com²MaC Conference on Applications of Group Theory to Combinatorics, Pohang, Korea, 9-12 July 2007. (©2008) - Unknown
No abstract available